Electrochemical Synthesis of Transparent, Amorphous, C60‐Rich, Photoactive, and Low‐Doped Film with an Interconnected Structure. Issue 12 (29th January 2013) - Li, Mao; Ishihara, Shinsuke; Ohkubo, Kei; Liao, Meiyong; Ji, Qingmin; Gu, Cheng; Pan, Yuyu; Jiang, Xiangfen; Akada, Misaho; Hill, Jonathan P.; Nakanishi, Takashi; Ma, Yuguang; et al.
<x xml:space="preserve">Abstract</x> An electrochemical synthesis is developed through quantitative electrochemical reaction of N‐alkylcarbazole leading to a novel class of structurally interconnected high‐C60 content (60 wt%) polymer films with negligible doping and intrinsic physicochemical properties of pure C60. This strategy allows preparation of previously unavailable low‐doped fullerene‐containing non‐conjugated polymers and broadens the potential applications of electrochemical synthesis for controlled polymer film structures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>